LO12: The utility of femoral nerve blocks in the emergency department; a national survey of practice. (15th May 2017) - Ringaert, J.; Broughton, J.; Pauls, M.; Laxdal, I.; Ashmead, N.
Abstract : Introduction: Approximately 30, 000 hip fractures occur annually in Canada, and the incidence will increase with an aging population. Pain control remains a challenge with these patients, as many are elderly and prone to delirium. Regional anesthesia has shown to be very effective with minimal risks, but it is not clear how often emergency physicians are using this technique to provide analgesia for patients with proximal hip fractures. This is the first Canada-wide survey to evaluate the use of regional anaesthesia in the emergency department for hip fractures. It also evaluates physician comfort level with performing these blocks, perceived educational needs in this area, and barriers to performing nerve blocks.Methods: A 13-question survey was sent to 1041 members of the Canadian Association of Emergency Physicians via email in January and February of 2016. Data was collected and analysed using an online collection program called "Survey Monkey". Ethics approval was obtained through the University of Manitoba Research Ethics Board.Results: 272 Emergency physicians and residents took part in the survey. The majority of respondents (75.9%) choose intravenous opioids as their first line of analgesia and only 7.6% use peripheral nerve blocks (PNB) as their first line choice for analgesia in hip fracture. In response to practitioner comfort with PNBs for hip fractures, most were not at all confident (45.0%) in their ability and many respondents have never performed a nerve block for a hip fracture (53.9%). The most commonly identified barriers to performing PNBs include lack of training, the time to perform the procedure and a lack of confidence. A larger percentage of respondents (34.2%), identified having had no training and no knowledge of how to perform PNBs for hip fractures.Conclusion: The vast majority of Canadian emergency physicians who took part in this survey do not utilize PNBs as a method of pain management for hip fractures. Over half have never performed one of these procedures and many have never received training in how to do so. Future efforts should focus on improving access to education, disseminating information regarding the effectiveness of PNB, and addressing logistical barriers in the ED.